Prediction of oxygen regime indicators in Danube river - V. L. Bezsonnyi; O. V. Tretyakov; A. N. Nekos; Ye. V. Chistov (Людина і довкілля: Проблеми неоекології)
Purpose. To identify the dynamics of the oxygen regime of the Danube River and to develop a model for forecasting the oxygen regime of the Danube based on the analysis of biochemical oxygen demand (BOD) and reaeration processes, taking into account the multifactorial influence of ecological, hydrological, and anthropogenic factors.